Meningkatkan Kemampuan Berhitung Permulaan Pada Anak Usia 5-6 Tahun Melalui Permainan Ular Tangga Di PAUD Hidayatut Taufiq Bekasi - Fikriyah , Zakiyatul; Priyanti, Nina Yuminar; Iskandar , Rhoma (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This study aims to determine the process of improving early numeracy skills in children aged 5-6 years through the snakes and ladders game at PAUD HIDAYATUT TAUFIQ. The research method is classroom action research. Classroom action research is action research to improve the quality of learning practices in the classroom. Based on the results of the research that has been done, it is known that snakes and ladders game activities can develop cognitive abilities in children aged 5-6 years at PAUD HIDAYATUT TAUFIQ Bekasi. This can be seen from the increase in children's cognitive abilities in each cycle. In the Pre-cycle there were no children who developed very well (BSB), in Cycle I children who developed according to expectations (BSH) with a percentage of 50%, while in Cycle II there was an increase to 81.25%. The conclusion that can be drawn is that through the snakes and ladders game can improve cognitive abilities in children aged 5-6 years at PAUD HIDAYATUT TAUFIQ Bekasi developed according to expectations (BSH) from Pre-cycle, Cycle I, Cycle II.